KERAGAAN USAHA AYAM RAS PEDAGING DI KECAMATAN PARUNG BOGOR: PERBANDINGAN USAHATERNAK MITRA DAN USAHATERNAK MANDIRI - Suryani Nurfadillah; Dwi Rachmina (Forum Agribisnis, 2015)
Broiler farming is one of the potential business, but this business has a high risk and requires substantial capital. One of the strategies that is used to overcome the problem is a partnership. Cogreg Village is one of the broiler producer areas in Bogor District. Most of the broiler farming in Cogreg are small and conventional farms. It is managed by a partnership which is different from broiler partnerships in general. The objectives of this study were to analyze the partnership and to compare the farm performance between partnership and independent broiler farm in Cogreg Village, Parung Subdistrict, Bogor Regency. This study used farm income analysis and R./C ratio method. The results showed that production, income, and the R/ C ratio of partnership member were higher than those of independent farmers on any scale. This proves that the partnership has a positive effect on broiler farming production and income. However, based on the qualitative analysis, it can be stated that the benefit sharing between farmers and firms is not balanced. The benefit received by the firm was much higher than that received by the farmer. The study recommends the need to establish a written partnership contract and improve maintenance management system, especially feed management.